Pembuatan Terra Preta dengan Sistem Pirolisis - . Yuliyanto (JURNAL CITRA WIDYA EDUKASI, 2020)
The purpose of this research is to determine the physical, chemical and biological properties of terra preta with biochar pyrolysis combustion systems. The addition of mycorrhizal fungi to enrich microorganism, which serves to increase nutrient absorption, increase plant resistance to biotic and abiotic stresses, maintain growth and production stability. Making terra preta is done with used wood and animal bones are burned with a pyrolysis system for 7 hours at a temperature of 500oC then activated with H2SO4 2M and mixing empty bunch, livestock urine, goat manure, mycorrhizal fungus, water used for washing rice and allowed to stand for 1 month in a state of condition covered, then mixed with mineral soil and allowed to stand for one month, then observed the physical, chemical and biological characteristics. The result of terra preta soil analysis, ie the texture of sand soil 13%, 50% dust, clay 37%, pH 7.2, Organic C 5.71%, N total 0.43%, C/N ratio of 13, P is available 634 ppm, CEC 23.45 cmolc/kg, and 150 spore/gr mycorrhiza content.